Analisis Lagu Pop Sunda “Jang” dan Relevansinya terhadap Layanan bimbingan dan konseling - Sutirna, Sutirna (IKIP Siliwangi, 2024)
English: The purpose of this study is to provide information on the form of guidance and counseling services through the Sundanese pop song